Assessing Technical Vocational Education and Training (TVET) Labour Market Potentials: Comparison of Conferees’ Opinions - Chukwu, Daniel Uchenna; Anaele, Edmund A.; Omeje, Hyginus Osita; Benedict Ohanu, Ifeanyi (Journal of Technical Education and Training, 2020)
Technical Vocational and Technical Education (TVET) has the potential to influence the labour market and transform the economy resulting in an improvement in the advancement of careers. This study assesses the potential of TVET to influence the labour market using the opinions of conferees. The study employs an integrative multi-method approach with a descriptive survey and focus group discussion. A structured questionnaire was used to collect data from 153 conferees using self-selection, non-probability sampling technique. Descriptive statistics of percentages and mean were used to analyze the data collected. Furthermore, the Keiser-Meyer-Olkin (KMO) measure of sampling adequacy gave MSA of .948; Bartlett’s Test of Sphericity showed p-value of 0.000, necessitating a factor analysis. The Kruskal-Wallis H Test was used to determine the statistical differences in the responses. Results revealed a gradual balance of gender in TVET with 53% female and 47% male; among the 99% employed in diverse sectors, only 18% (28) created jobs by themselves. Although there was coherence in agreement to TVET potentials, some respondents disagreed that TVET leads to good career opportunities. Findings show underlying strategy groupings to improve potential, in line with the focus group analysis, include: quality and upgraded learning environment, teachers and labour market information; relevant technical and employability skills, and established gender equality standards.